Study on surface roughness effect on shear behavior of concrete-soil interface. (March 2023) - Liu, Shan-wei; Zhang, Qian-qing; Ma, Bin; Li, Zhen-bao; Yin, Wei-ping; Lou, Qin-gang
Highlights: A large-scale constant normal stiffness cyclic shear apparatus was developed. The simulation method on the surface roughness of pile body was proposed. The relationship between the shear stress and the shear displacement of concrete-sand interface was established. Abstract: Concrete piles have been widely used in practice due to their large bearing capacity and small settlement. The roughness of concrete-soil interface has a significant influence on load transfer of piles and deformation between piles and soil. To investigate the surface roughness effect on shear behavior of concrete-soil interface, a series of laboratory shear tests, e.g., monotonic and cyclic shear tests, were carried out by using a self-developed large-scale constant normal stiffness (CNS) cyclic shear apparatus. In the laboratory shear tests, the simulation method on the surface roughness of pile body was proposed according to the measured hole diameter along the depth of in-situ bored piles, and concrete samples with different surface roughness values were formed by using carving machine. Based on the results of shear tests on the interface between concrete and standard sand under monotonic and cyclic shear, the relationship between the shear stress and the corresponding displacement was obtained, and the fitting relationship between the shear strength and roughness of concrete-sand interface was established. The shear displacement field of sand was analyzed by using a digital photogrammetric measurement software. The results show that the maximum thickness of the intense shear zone is observed to be 6.25 times the median particle diameters.